Adaptive functioning and behaviour problems in relation to level of education in children and adolescents with intellectual disability. - de Bildt A; Sytema S; Kraijer D; Sparrow S; Minderaa R (Journal of Intellectual Disability Research, 2005)
BACKGROUND: The interrelationship between adaptive functioning, behaviour problems and level of special education was studied in 186 children with IQs ranging from 61 to 70. The objective was to increase the insight into the contribution of adaptive functioning and general and autistic behaviour problems to the level of education in children with intellectual disability (ID). METHODS: Children from two levels of special education in the Netherlands were compared with respect to adaptive functioning [Vineland Adaptive Behavior Scales (VABS)], general behaviour problems [Child Behavior Checklist (CBCL)] and autistic behaviour problems [Autism Behavior Checklist (ABC)]. The effect of behaviour problems on adaptive functioning, and the causal relationships between behaviour problems, adaptive functioning and level of education were investigated. RESULTS: Children in schools for mild learning problems had higher VABS scores, and lower CBCL and ABC scores. The ABC had a significant effect on the total age equivalent of the VABS in schools for severe learning problems, the CBCL in schools for mild learning problems. A direct effect of the ABC and CBCL total scores on the VABS age equivalent was found, together with a direct effect of the VABS age equivalent on level of education and therefore an indirect effect of ABC and CBCL on level of education. CONCLUSIONS: In the children with the highest level of mild ID, adaptive functioning seems to be the most important factor that directly influences the level of education that a child attends. Autistic and general behaviour problems directly influence the level of adaptive functioning. Especially, autistic problems seem to have such a restrictive effect on the level of adaptive functioning that children do not reach the level of education that would be expected based on IQ. Clinical implications are discussed.